1986
DOI: 10.1007/bf00508784
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the antinociceptive effects of some adenosine analogues in the rat

Abstract: The antinociceptive effects of the stable adenosine analogues N6-phenylisopropyladenosine (L-PIA), N6-cyclohexyladenosine (CHA) and 5'-N-ethylcarboxamidoadenosine (NECA) were investigated in conscious rats using cutaneous thermal tests (hot plate and tail flick). Subcutaneous administration of the adenosine analogues induced a dose-dependent antinociceptive response for all agents. However, NECA was approximately 15 times more potent than PIA and CHA. Approximately the same potency order and response was seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…It is well known that adenosine regulates pain transmission at the level of the spinal cord, particularly by activating A 1 receptors. Intrathecal adenosine analogues or A 1 receptor agonists produce antinociception in behavioural studies [20,46]. Consistent with this, electrophysiological studies have demonstrated that adenosine directly hyperpolarises dorsal horn neurones [26,41] and inhibits glutamatergic transmission in the dorsal horn through activation of presynaptic A 1 receptors [22,23,41].…”
Section: Introductionmentioning
confidence: 91%
“…It is well known that adenosine regulates pain transmission at the level of the spinal cord, particularly by activating A 1 receptors. Intrathecal adenosine analogues or A 1 receptor agonists produce antinociception in behavioural studies [20,46]. Consistent with this, electrophysiological studies have demonstrated that adenosine directly hyperpolarises dorsal horn neurones [26,41] and inhibits glutamatergic transmission in the dorsal horn through activation of presynaptic A 1 receptors [22,23,41].…”
Section: Introductionmentioning
confidence: 91%
“…A 2B and A 3 receptors are widely distributed, but are present at a low density in the central nervous system (Feoktistov and Biaggioni, 1997;Rivkees et al, 2000). Within the spinal cord adenosine acts to suppress nociceptive signalling, mediated via the A 1 receptor (DeLander and Hopkins, 1986;Holmgren et al, 1986), while in the periphery it has an algogenic activity which may be mediated via an A 2 receptor subtype (McQueen and Ribeiro, 1986; see Sawynok and Yaksh, 1993). In the mouse the location of these receptors are most probably on sensory nerves as there is no A 2A receptor binding in the spinal cord (Bailey et al, 2002b;Kelly et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The role of adenosine receptors in nociception is complex and may involve different mechanisms in the central nervous system and in peripheral tissues. For example, spinal administration of adenosine receptor agonists produces antinociception in a variety of animal models of pain, presumably through the activation of spinal A 1 and to a lesser extent through A 2 receptors (Holmgren et al, 1986;Sawynok, 1998). Adenosine can produce analgesic or pronociceptive effects (Doak and Sawynok, 1995) through the activation of peripheral A 1 and A 2 receptors, respectively (Taiwo and Levine, 1990;Doak and Sawynok, 1995).…”
mentioning
confidence: 99%